CRISPR-Cas immunity: analysis of adaptation and interference reactions in prokaryotes - Cass, S.D.B. (2016)
Mobile genetic elements (MGEs, e.g. transposons, plasmids and phage) are an important driver of genetic diversity in microorganisms, and have diverse effects on microbe populations. Adaptation of Bacteria and Archaea to overcome negative effects of phage infection is sometimes referred to as an “arms race” that provokes the development of systems to protect against phage attack. One such defence is CRISPR-Cas, the topic of this research thesis. CRISPR (Clustered Regular Interspersed Short Palindromic Repeat) loci and Cas (CRISPR-associated) proteins are the molecular basis of this resistance mechanism. CRISPR-Cas can protect against phage and other foreign MGEs by incorporating a fragment of novel DNA into CRISPR (spacer acquisition) and using this as a template to generate a small RNA molecule, CRISPR RNA (crRNA), which targets the degradation of complementary sequences (interference). Effective interference requires formation of R-loop nucleic acid structure of crRNA base-pairing to homologous DNA, at positions flanked by PAM (Protospacer Adjacent Motif) sequence within the invader. This thesis investigates actions of CRISPR-Cas interference proteins, with focus on archaeal species Methanothermobacter thermautotrophicus (Mth) and Haloferax volcanii (Hvo). Mth and Hvo catalyse interference by utilizing a Cascade (CRISPR-associated Complex for Antiviral DEfence) protein-crRNA complex. Cas8, the large subunit protein in Cascade, was investigated to explain it’s essential role in interference. It is a PAM sensing protein that stabilizes R-loop formation to bring about interference. In addition, this analysis identified a surprising RNase activity of Cas8 that remains of unknown function. The thesis also details recent work on adaptation by Cas1 and Cas2 in Escherichia coli. Cas1 nuclease and transesterification activities upon replication fork intermediates are presented alongside a new model for spacer acquisition.